ORGANOLEPTIC QUALITY OF BALINESE BEEF MARINATED USING WULUH STARFRUIT (Averrhoa bilimbi L.) - R., Sihotang; Sriyani, N.L.P; Sriyani, N.L.P; Wibawa, A.A.P.P. (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
This study aims to find out the organoleptic quality of Balinese beef marinated using  wuluh  starfruit solution in different concentrations that was conducted at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University for two months, from September until October 2020. The design used in this study was a completely randomized design (CRD) with 4 treatments and 4 repetitions which was assessed by 15 semi-trained panellists. The four treatments were: The Balinese beef was soaked without wuluh starfruit solution (P0), The Balinese beef was soaked using wuluh starfruit solution at a concentration of 20% (P1), The Balinese beef was soaked using wuluh starfruit solution at a concentration of 40% (P2), The Balinese beef was soaked using wuluh starfruit solution at a concentration of 60% (P3). The variables observed were the organoleptic test which included color, odour, texture, taste, and overall acceptance. The results showed that the effect of Balinese beef marination using wuluh starfruit solution in different concentrations on organoleptic had a significant effect (P <0.05) on color, odour, taste, and overall acceptance. However, it had no significant effect (P> 0.05) on texture. The conclusion of this study was the Balinese beef marination using wuluh starfruit solution in different concentrations can affect the organoleptic quality of Balinese beef. The optimal concentration of wuluh starfruit solution to produce fine organoleptic quality Balinese beef was a concentration of 20%. It was seen from the panellists’ acceptance assessment of the color, texture, taste, and overall acceptance variables.             Keywords : concentration, organoleptic test, Balinese beef, wuluh starfruit